Vertebrate Sound Production and Acoustic Communication - Suthers, Roderick A.; Fitch, W. Tecumseh; Fay, Richard R.; Popper, Arthur N. (Springer Handbook of Auditory Research, 2016)
Vertebrate Sound Production and Acoustic Communication serves both as a tutorial introduction for newcomers and a springboard for further research for all scientists interested in understanding animal acoustic signals. Vertebrate Vocal Production: An Introductory Overview by W. Tecumseh Fitch and Roderick A. Suthers Fish Sound Production: An Exaptation? by Eric Parmentier and Michael L. Fine Vocal Sound Production and Acoustic Communication in Amphibians and Reptiles by Kaitlen Colafrancesco and Marcos Gridi-Papp Locomotion-Induced Sounds and Sonations: Mechanisms,Communication Function, and Relationship with Behavior by Christopher James Clark Embodied Motor Control of Avian Vocal Production by Daniel N. Düring and Coen P. H. Elemans Biophysics of Vocal Production in Mammalsby Christian T. Herbst Infrasonic and Seismic Communication in the Vertebrates with Special Emphasis on the Afrotheria: An Update and Future Directions by Peter M. Narins, Angela S. Stoeger, and Caitlin O'Connell-Rodwell Vocal Production by Terrestrial Mammals: Source, Filter, and Function by Anna M. Taylor, Benjamin D. Charlton, and David Reby Vocal Learning and Auditory-Vocal Feedback by Peter L. Tyack Vertebrate Bioacoustics: Prospects and Open Problems by W. Tecumseh Fitch About the Editors Roderick A. Suthers is Professor in the Medical Sciences program at Indiana University Bloomington. W. Tecumseh Fitch is Professor of Cognitive Biology at the University of Vienna. Richard R. Fay is Distinguished Research Professor of Psychology at Loyola University Chicago. Arthur N. Popper is Professor Emeritus and Research Professor in the Department of Biology at the University of Maryland, College Park. About the Series The Springer Handbook of Auditory Research presents a series of synthetic reviews of fundamental topics dealing with auditory systems. Each volume is independent and authoritative; taken as a set, this series is the definitive resource in the field.